Investigating the Security and Privacy Implications of Cloud-Based Disaster Recovery - Somaning Turwale (International Journal of Computational and Experimental Science and Engineering, 2026)
The article explores security weaknesses in cloud disaster recovery setups. One of the major concerns is that confidential information may be exposed unintentionally during replication. The article also highlights that if the recovery environment's access control is not robust, it can be a great exploit for hackers to gain unauthorized access. Furthermore, the privacy aspect is affected due to data residency and multi-tenant isolation issues. In the same article, it is pointed out that protection such as encryption, identity management, and network security controls is are way in which the system can be shielded against threats. The next paragraph talks about the need for having proper governance in place as a prerequisite for deploying security recovery architectures. Apart from that, regular reviews of the system, execution of data handling measures, and preparation for the response team in the event of an incident are also part of the organization’s playbook. The last sentence states that companies should not forget the challenge of striking a balance between the need to recover operations and protect data so as not to lose their resilience, and at the same time not break the rules.